One-Dimensional-Like Titania/4′-Pentyl-4-Biphenylcarbonitrile Composite Synthesized Under Magnetic Field and its Structure–Photocatalytic Activity Relationship - Abu Bakar, Nur I.; Chandren, Sheela; Attan, Nursyafreena; Leaw, Wai L.; Nur, Hadi (Frontiers in Chemistry, 2018)
The demonstration of the structure-properties relationship of shape-dependent photocatalyst remains a challenge today. Here, one-dimensional-like titania (TiO2), as a model photocatalyst, has been synthesized under strong magnetic field with the presence of magnetically responsive liquid crystal as the structure aligning-agent to demonstrate the relationship between the well-aligned structure and its photocatalytic properties. The importance of the one-dimensional-like TiO2 and its relationship with the electronic structures that affect the electron-hole recombination and the photocatalytic activity needs to be clarified. The synthesis of one-dimensional-like TiO2 with liquid crystal as the structure aligning-agent was carried out using sol-gel method under a magnetic field (0.3 T). The mixture of liquid crystal, 4’-pentyl-4-biphenylcarbonitrile (5CB), tetra-n-butyl orthotitanate (TBOT), 2-propanol and water, was subjected to slow hydrolysis under magnetic field. The TiO2-5CB was in well-aligned whisker-like shape when the reaction mixture was placed under the magnetic field, while an irregular shape of TiO2-5CB particles was formed when no magnetic field was applied. It shows that the strong interaction between 5CB and TBOT during the hydrolysis process under magnetic field controls the shape of titania. The intensity of the emission peaks in the photoluminescence spectrum of one-dimensional-like TiO2-5CB was lowered compared to the TiO2-5CB synthesized without the magnetic field, suggesting the occurrence of electron transfer from 5CB to the one-dimensional-like TiO2-5CB during ultraviolet irradiation. Apart from that, direct current (DC) electrical conductivity and Hall effect studies showed that the one-dimensional-like TiO2 composite enhanced the electron mobility. Thus, the recombination of electrons and holes was delayed due to the increase of electron mobility, hence, the photocatalytic activity of the one-dimensional-like TiO2 composite in the oxidation of styrene with the presence of aqueous hydrogen peroxide under UV irradiation was enhanced. This suggests that the one-dimensional-like shape of TiO2 composite plays an important role in its photocatalytic activity.